2013
DOI: 10.1111/nph.12309
|View full text |Cite
|
Sign up to set email alerts
|

Cotton plasma membrane intrinsic protein 2s (PIP2s) selectively interact to regulate their water channel activities and are required for fibre development

Abstract: Summary Aquaporins are thought to be associated with water transport and play important roles in cotton (Gossypium hirsutum) fibre elongation. Among aquaporins, plasma membrane intrinsic proteins (PIPs) constitute a plasma‐membrane‐specific subfamily and are further subdivided into PIP1 and PIP2 groups. In this study, four fibre‐preferential GhPIP2 genes were functionally characterized. The selective interactions among GhPIP2s and their interaction proteins were studied in detail to elucidate the molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 57 publications
2
51
2
Order By: Relevance
“…2a), existing as homo-tetramers (Fig. 2b), which was in accord with the classical structures for PIP (Chaumont et al, 2001;Li et al, 2013). Further analysis found that protein EU487188.1, EU487187.1 and AF118383.1 had higher similarity in structure with BnPIP-like protein than AF118381.1 had: AF118381.1 had 7 transmembrane domains and its Cterminal was extracellular (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…2a), existing as homo-tetramers (Fig. 2b), which was in accord with the classical structures for PIP (Chaumont et al, 2001;Li et al, 2013). Further analysis found that protein EU487188.1, EU487187.1 and AF118383.1 had higher similarity in structure with BnPIP-like protein than AF118381.1 had: AF118381.1 had 7 transmembrane domains and its Cterminal was extracellular (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…TdPIP2;1, as a PIP2 member in wheat, also possesses high water transport activity45. In cotton, expression of GhPIP2;3 also increased a high permeability coefficient of oocytes46. Similarly, tomato SlPIP2;1, SlPIP2;7 and SlPIP2;5 proteins displayed functional water channel activity which increased the osmotic permeability of the X. laevis oocytes 8- to 10-fold (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…In cotton, fiber elongation was found to depend on PIP2s and specific PIP2 isoform combinations markedly enhanced the water permeability in Xenopus oocytes (Li et al, 2013). Also, in the halophyte, Thellungiella halophila , ThPIP1 interacted with ThPIP2 and a non-specific lipid-transfer protein 2, suggesting a role of ThPIP1 in the response to the external signals that trigger multiple physiological processes when plants are exposed to salinity (Qiang et al, 2015).…”
Section: Protein–protein Interactionsmentioning
confidence: 99%